Reconsidering Clement of Alexandria’s Protrepticus Book 2 as evidence for Dionysiac Mystery Ritual - Etsebeth, Nuraan (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.